Range migration compensation for moving targets in chirp radars with stepped frequency. Issue 19 (5th July 2019) - Sen, Wang; Qinglong, Bao; Zengping, Chen
Abstract : Long‐time coherent pulse integration method has been extensively used in detecting weak targets, but the detection performance is affected by range migration (RM) due to high radial velocity. This study proposes a new modulation format of chirp radars with stepped frequency and a corresponding coherent integration method based on adjacent cross‐correlation operation (ACCO) to compensate RMs of moving targets with, respectively, arbitrary unknown constant velocity. Simulation results show that the method has higher range resolution compared with bandwidth variation modulation and shorter blind distance compared with duration variation modulation.